Impact of COVID-19-associated Mucormycosis in Kidney Transplant Recipients: A Multicenter Cohort Study. Issue 1 (13th December 2021) - Meshram, Hari Shankar; Kute, Vivek B.; Yadav, Dinesh Kumar; Godara, Suraj; Dalal, Sonal; Guleria, Sandeep; Bhalla, Anil K.; Pathak, Vivek; Anandh, Urmila; Bansal, Shyam; Patel, Himanshu; Hegde, Umapati; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: COVID-19-associated mucormycosis (CAM) is a recently emerging entity. There is a lack of reports of CAM in organ transplant recipients. Methods: We conducted a multicenter (n = 18) retrospective research in India during November 2020 to July 2021. The purpose of this study was to explore the clinical spectrum, outcome and risk factors for mortality of CAM in kidney transplant recipients (KTRs). Results: The incidence of CAM was 4.4% (61/1382 COVID-19-positive KTRs) with 26.2% mortality. The median age of the cohort was 45 (38–54) y. Twenty (32%) were not hospitalized and 14 (22.9%) were on room air during COVID-19. The proportion of postdischarge CAM was 59.1%, while concurrent CAM was reported in 40.9%. The presentation of CAM was 91.8% rhino-orbital-cerebral mucormycosis and 8.2% pulmonary with 19.6% and 100% mortality, respectively. In the univariable analysis, older age, obesity, difficulty of breathing, high-flow oxygen requirement, and delay in starting therapy were significantly associated with mortality. In the multivariable logistic regression analysis, patients requiring high-flow oxygen therapy [odds ratio (95% confidence interval) = 9.3 (1.6-51); P = 0.01] and obesity [odds ratio (95% confidence interval) = 5.2 (1-28); P = 0.05] was associated with mortality. The median follow-up of the study was 60 (35–60) d. Conclusions: We describe the largest case series of CAM in KTRs. Morality in pulmonary CAM is extremely high. Severe COVID-19 pose extra risk for the development of CAM and associated mortality. Our report will help in better understanding the conundrum and management of CAM.